2014
DOI: 10.5216/ree.v16i1.20315
|View full text |Cite
|
Sign up to set email alerts
|

Desobstrução ineficaz de vias aéreas em crianças com infecção respiratória aguda

Abstract: Desobstrução ineficaz de vias aéreas em crianças com infecção respiratória aguda Ineffective airway clearance in children with acute respiratory infectionDesobstrucción ineficaz de vías aéreas en niños con infección respiratoria aguda

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
6
0
4
Order By: Relevance
“…A desobstrução ineficaz de vias aéreas é uma manifestação clínica comum nessa população devido à anatomia característica da idade, o que demanda intervenção rápida e resolutiva a este sinal (18) . Durante a consulta, os pais são orientados a instilar 0,5 ml de soro fisiológico (0,9%) em cada narina de 3/3h antes das mamadas e posicionar o bebê em decúbito dorsal ou lateral com a cabeceira elevada.…”
Section: Resultsunclassified
“…A desobstrução ineficaz de vias aéreas é uma manifestação clínica comum nessa população devido à anatomia característica da idade, o que demanda intervenção rápida e resolutiva a este sinal (18) . Durante a consulta, os pais são orientados a instilar 0,5 ml de soro fisiológico (0,9%) em cada narina de 3/3h antes das mamadas e posicionar o bebê em decúbito dorsal ou lateral com a cabeceira elevada.…”
Section: Resultsunclassified
“…Thirty-three studies were found, that supported the construction of the definitions of the terms of DE under study. Of the selected articles, the following journals stood out: Nine studies were conducted in Europe (England, Spain, Germany, Italy, Portugal and France); 28-35,41 six in South America (Brazil); [36][37][38][39][40]42 three in North America (US); one in Oceania (Australia); 46 one in Asia (Korea) 47 and a multicenter study involved countries from several continents (Asia, Europe and America); 48 In terms of language, 14 studies were in English; 28-32,34-5,40,43-8 six in Portuguese 36-9,41-2 and one in spanish. 33 The studies consisted of five cohorts; 31-2,35,47-8 four methodological studies; two literature reviews; 30,44 two clinical trials 33,40 and a qualitative study; 46 Regarding the approach, five studies used the cross-sectional approach; 29,34,45 one, the retrospective approach 28 and one study is descriptive-correlational with cluster analysis; 41 out of 12 studies [28][29][31][32][33][34][35]41,[45][46][47][48] developed with adults, four occurred in hemodialysis environment with chronic renal patients 28, [33][34]41 and five studies were developed with children.…”
Section: Methods Objectivementioning
confidence: 99%
“…33 The studies consisted of five cohorts; 31-2,35,47-8 four methodological studies; two literature reviews; 30,44 two clinical trials 33,40 and a qualitative study; 46 Regarding the approach, five studies used the cross-sectional approach; 29,34,45 one, the retrospective approach 28 and one study is descriptive-correlational with cluster analysis; 41 out of 12 studies [28][29][31][32][33][34][35]41,[45][46][47][48] developed with adults, four occurred in hemodialysis environment with chronic renal patients 28, [33][34]41 and five studies were developed with children. [36][37][38][39][40] The articles included in this review are characterized in Figure 2 according to title, country, objectives, level of evidence 16 and year of publication. At the time of the research proposal, as well as at the beginning of the data collection, the RF and DC of the DC under study were considered as elements to be evaluated, according to the NANDA-I version (2015-2017).…”
Section: Methods Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Esse resultado também foi encontrado no estudo realizado em uma unidade de Pediatria hospitalar (12) , em que se identificou a frequência de 100% para o diagnóstico desobstrução ineficaz das vias áreas, 80% para o diagnóstico padrão respiratório ineficaz e 66,7% para o diagnóstico risco de infecção. Outra pesquisa (13) corrobora com esse estudo, onde se identificou frequência diminuída do diagnóstico de enfermagem desobstrução ineficaz de vias aéreas em 151 crianças internadas em um hospital público pediátrico, que corresponde a apenas 37,7% da amostra.…”
Section: Diagnósticos De Enfermagem Prevalentes Na Pediatriaunclassified